1999
DOI: 10.1080/13811119908258311
|View full text |Cite
|
Sign up to set email alerts
|

Depressed inpatients, electrodermal reactivity, and suicide - a study about psychophysiology of suicidal behavior

Abstract: This study deals with the psychophysiological (electrodermal reactivity in a habituation experiment, habituation score) basis of suicidal behaviour. It shows habituation data of 30 suicides with violent method compared to age-and sex-matched control groups with different suicidal expressions, on a large database of a total sample of 504 depressed inpatients.The major finding of a significantly reduced electrodermal reactivity (habituation score) in suicidal action versus suicidal thinking confirms early result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…Publications concerning ‘electrodermal activity’, ‘suicide’, ‘suicide attempt’ and ‘depression’ were searched in PubMed and PsychINFO and through references from 66 known publications within the field of electrodermal activity in depression since 1890. There were 31 available reports in electrodermal suicidology (3–31).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Publications concerning ‘electrodermal activity’, ‘suicide’, ‘suicide attempt’ and ‘depression’ were searched in PubMed and PsychINFO and through references from 66 known publications within the field of electrodermal activity in depression since 1890. There were 31 available reports in electrodermal suicidology (3–31).…”
Section: Methodsmentioning
confidence: 99%
“…Those reports were selected in a first step that addressed the habituation of the electrodermal response to simple tone stimuli in depressed patients. Excluding on the present issue less focused and closely interrelated reports as a second step, ten studies from 1986 to 2007 remained (3–12) and described in Tables 1–2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second potential biological vulnerability for development of the capability for suicide involves the rate at which individuals habituate at the neurobiological level. Research has demonstrated that individuals with a history of a suicide attempt, particularly violent attempts, and those who later died by suicide exhibit faster rates of basic physiological habituation during a tone stimuli noise task (Edman, Asberg, Levander, & Schalling, 1986; Wolfersdorf, Straub, Barg, Keller, & Kaschka, 1999). Such quicker acting habituation processes may be problematic as even minor diathesis‐expressing life experiences (e.g., playing contact sports or non‐life‐threatening accidental injury) may greatly facilitate the habituation to fear and pain.…”
Section: The Acquired Capability For Suicidementioning
confidence: 99%
“…A trend to a faster habituation in suicidal attempters and completers who have used violent methods was also confirmed by Keller et al [18] and Wolfersdorf & Straub [19]. Differently, Jandl et al [20] found no difference between violent and non-violent suicide attempters, even if suicide attempters were significantly more hyporeactive than non-attempters.…”
Section: Introductionmentioning
confidence: 72%